Aspen modeling for MEA–CO2 loop: Dynamic gridding for accurate column profile. (June 2015) - Fan, Zhen; Liu, Kun; Qi, Guojie; Frimpong, Reynolds; Nikolic, Heather; Liu, Kunlei
Highlights: Fine gridding is required for properly solving the column model. Rate-based column profiles are significantly impacted by the gridding. Convergence successfully obtained by using dynamic gridding to match gradient profiles. Matching the absorption rate profile is much more important than matching the inlet and outlet parameters only when a rate-based model applied. Abstract: This paper deals with modeling of post-combustion CO2 removal by using a chemical solvent with an absorption–stripping loop. An Aspen Plus ® rate-based model is applied for the packed column. It has been found in the literature that there is a stability issue related to the number of stages used, especially with a tall column for a high capture efficiency and for a low specific heat duty (MJ/kg CO2 ). For the same configuration and operating condition initial setup, the column temperature and concentration profile obtained shifts and varies dependent upon the number of stages. Mathematically, the number of stages applied for a packed column is equivalent to the number of cells (stages) used for solving the column model. It is well known that the stage size will play an important role in stability of the numerical solution. To improve the stability and to minimize the variation of column profile, a variable stage size has been applied which consists of varying the stage size dynamically for different parts of the column in correspondence to a varied temperature gradient and component profile, i.e., to the absorption rate profile. The resulting resolution provides more robust column profiles with additional details, especially with respect to the column temperature profile since absorption kinetics and chemical reaction enhanced mass transfer are all coupled together with temperature and reactant concentration profiles. The presented method of dynamic gridding is not only capable of successfully solving convergence problems, but also of mathematically generating more accurate column profiles for absorption performance analysis. This method can be applied for integration of CO2 removal with a power plant in a complex system.